Pengaruh volatilitas harga minyak, kurs, dan BI rate terhadap indeks harga saham gabungan 2018-2022 - Yohanes, Yohanes; Setyawan, Ignatius Roni (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
Macroeconomic factors that could influence IDX’s (JKSE) composite stock price index are crude oil prices, exchange rates from Rupiah to the US dollar, and BI rate. These are three independent variables that take into account several factors and situations in the world economy. The prices of crude oil are an indication of global demand. The exchange rate is based on the economic situation in Indonesia. In response to economic conditions in Indonesia, the Bank of Indonesia has a policy based on the BI Rate. These three variables indicate that when the economy is strong, the stock index also strengthens. The use of the TARCH method explains the volatilities of independent variables and their influence on dependent variables. The TARCH method is used when asymmetric volatility is present. The results of this research show crude oil prices and BI Rate positively and significantly affect the JKSE. This means when the economic condition is strong, the stock index will also be affected positively. While the Rupiah exchange rate has a negative and significant impact. This is because if the conversion rate decreases (Rupiah strengthens), it indicates that the Indonesian economy is strong. Simultaneous tests also show that all three variables influence the JKSE. These variables are examined to understand the impact of macroeconomic variables on the stock index, so readers are expected to have insights into the global economic situation before investing in stocks.